Escape behaviour of female field crickets is not affected by male attractiveness, but shows consistent patterns within individuals. Issue 2 (3rd March 2020) - Kuriwada, Takashi
Abstract : Predator avoidance is one of the most important fitness components because predation success is directly linked to prey death. Decision making regarding predator avoidance is influenced by many abiotic and biotic factors because of the trade-off between predator avoidance and other contextual behaviours. Attractive sexual signals may elicit responses not only from potential mates, but also from predators. Therefore, female escape behaviour will be affected by the attractiveness of male signals. I examined the effect of attractiveness of male calling songs on the components of female escape behaviour [i.e., responsiveness to artificial predatory stimuli, alternative escape tactics (jumping or forward locomotion), and locomotor distance] in the field cricket Teleogryllus occipitalis . Although song attractiveness did not affect female escape behaviour, behavioural components showed high inter-individual variation. The results showed that escape behaviour exhibited high repeatability, and the consistency affects decision-making in terms of escape behaviour in field crickets.